Some risks of the legitimation of the right through consensus and procedure - Carrasco Astudillo, Gonzalo (Derecho Público Iberoamericano, 2022)
This essay aims to warn about some risks of conceiving the legitimation of law through consensus and procedural structures for its formation, such as totalitarianism, the loss of the concept of truth and the instrumental use of the legal order for the imposition of the strongest by on the weak.